LC–MS-based lipidomic analysis of liver tissue sample from spontaneously hypertensive rats treated with extract hawthorn fruits - Sun, Luping; Chi, Bingqing; Xia, Mingfeng; Ma, Zhen; Zhang, Hongbin; Jiang, Haiqiang; Zhang, Fang; Tian, Zhenhua (Frontiers in Pharmacology, 2022)
At present, many experiments provide support for the cardiovascular protective effect of hawthorn (Crataegus oxyacantha) flower, leaf and fruit extracts. The aim of this study was to investigate the intervention mechanism of hawthorn fruit extract on spontaneously hypertensive rats (SHR) and its effect on their lipid metabolic pattern. After SHR was intervened by hawthorn extract (1.08 g/kg/d) for 6 weeks, the blood pressure and liver histopathology of rats were evaluated. An UHPLC-Q Extractive metabolomics approach was used to collect information on rat liver lipid metabolites, combined with multivariate data analysis to identify significantly different substances and potential biomarkers through mass spectrometry and database searches. Histomorphology of the liver was partially restored in the hawthorn-treated group. Hawthorn extract interferes with sphingolipid metabolism, glycerophospholipid metabolism and glycerolipids metabolism, improving partially disturbed metabolic pathways. This study showed that hawthorn could partially restore liver histomorphology and has anti-hypertensive effect by regulating lipid metabolism.